PEMBUATANROTI MANIS DARI TEPUNG KOMPOSIT (TEPUNG TERIGU, PATI SAGU, TEPUNG UBI JALAR UNGU) - Hendra ' Saputra; Vonny Setiaries Johan; Rahmayuni ' ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this study was to obtain the best formulationin composite flour (wheat flour, sago starch, purple sweet potato flour)quality and nutritional value of sweet bread and meet SNI 01-3840-1995. This research was carried out experimentally using completely randomized design (CRD) with five treatments and three replications. The treatment in this study were R1 (70% wheat flour + 0% sago starch + 30% purple sweet potatoflour), R2 (70% wheat flour + 10% sago starch + 20% purple sweet potatoflour), R3 (70% wheat flour + 20% sago starch + 10% purple sweet potato flour) and R4 (70% wheat flour + 30% sago starch + 0% purple sweet potato flour).Data obtained were treated by the analysis of variance followed by Duncan New Multiple Range Test (DMRT) at level 5%. The results showed that the addition of sago starch and purple sweet potatoflour at different concentration levels significantly effect on the moisture content, ash content, fat content, hedonic test, descriptive test of colour, aroma, and texture of sweet breadand significantly effect on the descriptive test the flavor. The best treatment is a sweet bread R2(70% wheat flour + 10% sago starch + 20% purple sweet potatoflour). with a moisture content of 25.41%, ash content of 0.85%, fat content of 6.78% and the level development of 6.50, as well as sensory acceptable by panelist. Keywords: Sweet bread, Sago starch, purple sweet potato flour.